In vivo test of a radiography‐based navigation system for control of derotational osteotomies. Issue 1 (29th June 2020) - Grünwald, Leonard; Schröter, Steffen; Windolf, Markus; Gueorguiev, Boyko; Richards, Geoff; Buschbaum, Jan
Abstract: Malalignment of the femur is a frequently encountered problem in orthopaedics entailing manifold consequences for the affected patients. Corrective osteotomies, necessary to restore the physiological and anatomical relationships, face great challenges due to no existing reliable gold standard for intraoperative control of torsional malalignment. The aim of this study was to test a novel radiography‐based navigation tool for control of derotational osteotomies in a clinical environment. In a first—and preliminary—case‐controlled study on 12 patients (level 3 of evidence), the achieved torsional correction measured with implementation of the navigation tool was compared with measurements from pre‐ and postoperative computed tomography (CT) scans. The navigation tool was able to acquire and process all relevant data and capture possible malrotation during surgery with only little deviations of 1.61° ± 0.86° (mean ± standard deviation) from the measurements based on CT scans. Next, the system will be used to assist surgeons for more precise treatment avoiding maltorsion after derotational osteotomies.